Relationship marketing strategy and its impact on achieving customer loyalty: an analytical exploratory study of the opinions of a sample of employees and customers of Iraqi private banks - Fouad Hamoudi Al Attar; Ahmed Abdull Abbas (Iraqi Journal for Administrative Sciences, 2025)
This study is taking a role of marketing , within the relations, describe it as an independent variable in its dimensions (measurements) as if (Trust , commentment, communication and the satisfaction), to a chive the customer’s loyalty by describing it as a "variable" depending on its figures or indicators represented by ( behaviors and situations ) as an exploration and analysis study to a certain opinions for certain , commercials and private sectors of Iraqi banks. While this study tried to give answers to all queries: like :- -what is the level of performing the marketing within the relations in the commercial and private sectors of Iraqi banks , within the study and the range of concerning to its dimensions ? -what is the level of concerning of these banks within the study of the indicators of the client loyalty? -what is the level of clients loyalty for who are dealing with private sector banks , combined with the study ? -is there any relation influence between the marketing and the indicators of client’s loyalty? -This study is looking for achieving certain aims like as :- 1- Detect the range of banking performance under the study of marketing connected to relations . 2-Identiy the level of customer’s loyalty in the banks under study . 3-Test the affects between the marketing and its relation with the customers loyalty . To achieve the aims of the study , hypothetical ( diagram ) . it was constructed , determined the nature of relation in between , the independent variable and dependent one, and emerge through it , some main hypothesis were tested by using flocks of statistics means of the commercial and private sector of Iraqi banks presented by ( Baghdad Al-shimal Al- eqtissad Al-mutahed Al- Ahliee Al- Mansoor ) as a field to do the study and “exam” its hypothesis and it used the” questionnaire form” as a main tool to collect the data which is related with that field , it was contributed on a sample went to(90) from employees and clients in these banks within the study .This study reached to a certain conclusion , the mpst important of it :- -there is a relation influence objected statistics indicator in between the strategy of marketing with the relations and the client loyalty for these commercial and private sector Iraqi banks within the study .The study went out with a certain recommendations first of it :- ( to do the application in marketing and the relations , requires support the top management , to publish and depend the banking culture , concentrate on the service of the customer )